Menggagas Sistem Informasi Akuntansi Prophetic (Constructing Prophetic Accounting Information System) - Kusdewanti, Amelia Indah (STIE Malangkucecwara, 2022)
This article aims to critique and construct prophetic accounting information system (AIS). This article uses the metaphor of the Kaaba and tawaf as a method. Meanwhile, the author uses the submission theory initiated by Kusdewanti et al. (2016) as a framework of thought. Kaaba is a value center that connects various aspects of stakeholders to vertically and horizontally, while tawaf places SIA as a basic movement connector that surrounds the value center. As a connector, SIA Prophetic is based on cosmological values, so that its technological aspects will also be based on religious-social-culture. The input is immaterial and material, the process is participatory, and the information output is based on Falah. This article helps build a more humanist AIS and a technology for accounting that is based on religion, culturally, and socially.